1997
DOI: 10.1530/eje.0.1370387
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin in short children born small for gestational age: relationship with the growth response to growth hormone treatment. The Swedish Study Group for Growth Hormone Treatment

Abstract: The product of the obese (ob) gene, leptin, is an adipocyte-derived hormone that is involved in the regulation of appetite and body weight. This study was undertaken in order to describe the basal serum levels of leptin in prepubertal short children born small for gestational age (SGA) and their relationship with growth parameters, before and during growth hormone (GH) treatment. Eighty-nine prepubertal short children (66 boys, 23 girls; height standard deviation score (SDS), ¹5.4 to ¹2.0; age, 2.0 to 12.8 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 47 publications
(44 reference statements)
4
26
0
Order By: Relevance
“…These factors have a clear role in fetal growth as they are found at lower levels in pregnancies complicated by intrauterine growth restriction (20,35). Although this is merely an association, we speculate that HO may play a role in intrauterine growth.…”
Section: Discussionmentioning
confidence: 71%
“…These factors have a clear role in fetal growth as they are found at lower levels in pregnancies complicated by intrauterine growth restriction (20,35). Although this is merely an association, we speculate that HO may play a role in intrauterine growth.…”
Section: Discussionmentioning
confidence: 71%
“…Woods et al reported that short prepubertal SGA children have lower leptin levels than their short control children with normal birth weight (7). According to Boguzewski et al, SGA children, with an age range of 2.0 to 12.8 years, had lower leptin levels than AGA children of the same age range (23).…”
Section: Discussionmentioning
confidence: 98%
“…In puberty, leptin levels decrease in boys, while the levels continue to increase in girls (22). In SGA children, leptin levels have been reported to be lower than in AGA children (23).…”
Section: Introductionmentioning
confidence: 97%
“…The long-term impact of foetal growth – such as its association with cardiovascular diseases – has been observed and attracted much attention in recent years [51, 52, 53]. It has been known that infants born small- for-gestational age had much lower levels of neonatal and childhood serum leptin, insulin-like growth factor-I and insulin-like growth factor binding protein-3 [54, 55, 56, 57, 58]. We can thus speculate that this subnormal neonatal hormone profile at birth may have a long-term imprinting effect on the postnatal timing of puberty, although the mechanism for this is unclear.…”
Section: Nutrition and Sexual Maturationmentioning
confidence: 99%